Detection of Helicobacter pylori in gastric cancer tissue through histopathology, immunohistochemistry and real-time reverse transcription-PCR - Castaneda, Carlos A (2020)
Aim:Helicobacter pylori is usually detected based on hematoxylin-eosin (H-E) features, but, immunohistochemistry (IHC) and real-time PCR (RT-PCR) are more precise in chronic-gastritis. We evaluated the relevance of these tests in Peruvian gastric cancer samples. Materials & methods: We performed and evaluated H-E, IHC staining and RT-PCR in 288 gastric tumors. Slides were independently evaluated by three pathologists. Results:H. pylori was detected in 167/287 through H-E, 140/288 through IHC and 175/288 through RT-PCR, and positive-status were associated (p < 0.001). H. pylori detection by H-E had a good concordance with IHC (kappa index = 0.632) but poor with RT-PCR (kappa index = 0.317). Higher median gene-copies were found in high H. pylori density through H-E or IHC (p < 0.001). Conclusion: H-E evaluation is accurate in gastric cancer, and IHC and RT-PCR can complement its results.